The String Theory: Past and Present. Issue 1 (February 2021) - Chen, Beibei
Abstract: String Theory is a theory that could be a candidate for "Theory of Everything." It does not have a long history, as many scientists had witnessed it evolved overtime. The theory is still considered unprovable today. Since lesser scientists are still focusing on this theory in the present time, this passage will be focusing on how it was developed and explains why it was still a problem left for future generations.